Isolation and Characterization of Human Gut Bacteria Capable of Extracellular Electron Transport by Electrochemical Techniques - Naradasu, Divya; Miran, Waheed; Sakamoto, Mitsuo; Okamoto, Akihiro (Frontiers in Microbiology, 2019)
Microorganisms are known to exhibit extracellular electron transfer (EET) in wide variety of habitats. However, as for human microbiome which significantly impacts our health, the role and importance of EET has not widely investigated. In this study, we enriched and isolated EET-capable bacteria from human gut microbes using electrochemical enrichment method, and examined whether the isolates couple EET with anaerobic respiration or fermentation. Upon the use of energy rich or minimum media (with acetate or lactate) for electrochemical enrichment with human gut sample at electrode potential of (+0.4 V vs SHE), both culture conditions showed significant current production. However, EET-capable pure strains were enriched specifically in minimum media, and subsequent incubation using 𝛿-MnO2-agar plate with lactate or acetate led to the isolation of two EET-capable microbial strains, Gut-S1 and Gut-S2, with 16S rRNA gene sequence 99.9% identity with Enterococcus avium and Klebsiella pneumoniae, respectively. While enrichment involved anaerobic respiration with acetate and lactate, further electrochemistry with E. avium and K. pneumoniae revealed that the fermentation of glucose also coupled with EET. These results suggest EET coupled not only with anaerobic respiration, but also with fermentation in human gut, which implies different role of EET from that in environmental bacteria that couples EET with anaerobic respiration. Furthermore, given E. avium and K. pneumoniae are pathogen, outstanding of survival competition on electrochemical condition suggests that fermentative EET may link with pathogenicity in guts environment.